Socio-economic inequality in health: Individual- and area- level measures of socio-economic position - Middleton, Nicos; Ellina, Panayiota; Zannoupas, George; Lamnisos, Demetris; Kouta, Christiana (My University, 2018)
Socioeconomic position (SEP) refers to the relative place an individual or a social group holds within the structure of society. SEP is determined by a multitude of factors, from individual and household circumstances across the life course to social processes operating at higher levels. Even though a complex construct, it is often operationalized using single person-based indicators and/or subjective measures of an individual’s own perceived position in the social ladder. Furthermore, recognizing that social stratification is geographically defined, area-based measures place a community in the socioeconomic disadvantage continuum and are used to quantify the magnitude of geographically defined social inequalities Data driven approaches have been mostly used to construct socioeconomic deprivation indices, commonly using census-based indicators which reflect the sociodemographical compositions of areas. Increasingly, a wider set of methods are been used to capture features of a community’s environment pertaining to the physical, built and social environment.
Keywords: Socio-economic inequality; Health